Using the COVID-19 pandemic as fresh lenses to generate a thicker analysis of four research theories on discipleship within a Reformed congregation - Kaze Yemtsa, Bachelard (Practical theology, 2021)
Tragedies can potentially betray some of our true colours. The COVID-19 pandemic has created a unique pastoral matrix and dynamic. This has had significant implications on the expression of congregants’ identities and frames of meaning-making. The usually gathered congregation was disoriented, traumatised, as well as physically ‘scattered’ and ‘disembedded’ during the lockdown season. This dynamic has enabled me to have a fresh appreciation of my research into discipleship in a Reformed congregation, where I am the ordained minister. I had carried out a congregational study on evangelistic discipleship before the pandemic. I have used the disruption caused by the COVID-19 pandemic to reread four initial research assertions about discipleship: covenantal, gathered, vicarious, and pragmatic. This re-reading is anchored on five pastoral observations, regarding isolation, fellowship, gifts/ skills, prayer, and the human–Divine relationship. This revision of data analysis has re-clothed, nuanced and expanded my initial data interpretation. The ethnographic approach acted like a pair of fresh eyes and a critical friend. It has enabled me to reread ordinary identities in extraordinary circumstances.